2020
DOI: 10.1038/s41417-020-00245-w
|View full text |Cite|
|
Sign up to set email alerts
|

ERK3/MAPK6 is required for KRAS-mediated NSCLC tumorigenesis

Abstract: KRAS is one of the most frequently mutated oncogenes, especially in lung cancers. Targeting of KRAS directly or the downstream effector signaling machinery is of prime interest in treating lung cancers. Here, we uncover that ERK3, a ubiquitously expressed atypical MAPK, is required for KRAS-mediated NSCLC tumors. ERK3 is highly expressed in lung cancers, and oncogenic KRAS led to the activation and stabilization of the ERK3 protein. In particular, phosphorylation of serine 189 in the activation motif of ERK3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 39 publications
(42 reference statements)
2
34
0
Order By: Relevance
“…To our knowledge, our study is the first revealing a bona fide tumor-promoting role for ERK3 in vivo using genetically engineered mouse models. Together with previous findings showing important roles of ERK3 in cultured cells and in xenograft lung tumor model [3,6], our findings corroborate that ERK3 acts as an oncoprotein in promoting LUAD development and progression.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…To our knowledge, our study is the first revealing a bona fide tumor-promoting role for ERK3 in vivo using genetically engineered mouse models. Together with previous findings showing important roles of ERK3 in cultured cells and in xenograft lung tumor model [3,6], our findings corroborate that ERK3 acts as an oncoprotein in promoting LUAD development and progression.…”
Section: Discussionsupporting
confidence: 90%
“…The kinase activity and cellular functions of ERK3 are positively regulated by phosphorylation of S189 in the activation motif, although it remains elusive regarding the upstream signal for stimulating S189 phosphorylation [5,[39][40][41]. Importantly, the level of S189 phosphorylation, which was determined by mass-spectrometry-based phosphoproteomic analyses in the study, was shown to be significantly elevated in lung adenocarcinomas [6]. These clinic findings suggest that altered ERK3 signaling in cancers is mainly caused by upregulation of expression level and posttranslational modifications rather than genetic mutations.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations